To compare the effects of intra vaginal prostaglandin E1 and intra-cervical prostaglandin E2 for prelabour ripening of unfavorable uterine cervix in nulliparous women - Jain, Shikha A.; Chakravarti, Nisha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour by use of prostaglandins improves the obstetric outcome in complicated cases such as prolonged deliveries. The aim of the present study was to compare the effect of prostaglandin E1 (PGE1) and prostaglandin E2 (PGE2) for prelabour ripening of unfavourable uterine cervix in nulliparous women, to study the effect of PGE1 and PGE2 on duration of labor and to evaluate the obstetrical and neonatal outcome of induction of labour using prostaglandins E1 and E2. Methods: This was a prospective study conducted on 50 nulliparous women with singleton pregnancy with gestational age ≥37 weeks during the period from August 2008 to October 2010 in the Department of Obstetrics and Gynaecology of Bombay Hospital Institute of Medical Sciences and Allied Hospitals, Mumbai. All the 50 patients were divided into two groups. Group-1 containing 25 patients received intravaginal PGE1, (Tablet Misoprostol 25 mcg) inserted in the posterior vaginal fornix under all aseptic precautions. Group-2 containing 25 patients received intracervical PGE2, (Dinoprostone gel, 0.5 mg). Analysis and comparison of various parameters like induction- delivery interval, Bishops score before and after administration of drug, mode of delivery, neonatal outcome, foeto-maternal complications between the two groups were noted and analysed the data statistically by using Chi-square, continuity correction, Fisher’s exact test and Mann-Whitney tests. Results: Majority of the patients in both the groups were under the age of 23-27 years. Post-datism was the common indication noticed in 18 (72%) and 13 (52%) patients of both the groups respectively. Maximum patients had a Bishop’s score of 3 in PGE1 (56%) and PGE2 groups (48%) respectively. The improvement in Bishop’s score in both the groups before and after drug administration was 6.20 and 6.76 respectively. Maximum patients in both the groups went into active labour within six hours of induction of labour. The most common side effects seen in our study was nausea and vomiting in both groups. Majority (23) were born with Apgar score 8-10 in group 1 and 21 for group 2 patients. Conclusions: Both the drugs had similar efficacy and safety in induction of labour. Prospective research is required to fully evaluate the impact of AMOR-IPAT on nulliparous birth outcomes.